Gambaran Kehidupan Wanita yang di Poligami - Khasan, Mohammad; Sujoko, Sujoko (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
The phenomenon of polygamy in Indonesia is still a polemic in society. One of them was during the speech by the chairman of Indonesian Solidarity Party (PSI) Grace Natalie at East Java Expo on Tuesday (11/12/2018) which stated that "PSI will never support polygamy". The objective of this study is to find out how the life phenomenon on polygamous women in Surakarta. The method used is a qualitative approach using interviews as a method of collecting data. The results of this study indicate that basically women who will be polygamous will emerge various kinds of feelings such as: distrust, sadness, anger, disappointment, and hurt. Nevertheles, a woman must obey or accept whatever her husband wants, this is due to the child, the future wife is pregnant out of wedlock, threatened to be divorced, and orders from God in Islamic law.